2004
DOI: 10.1136/pgmj.2003.010553
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to physical activity in patients with diabetes

Abstract: Purpose: Two questions were addressed: (1) How much physical activity do patients with diabetes perform? (2) What are the perceived factors that prevent patients from doing more physical activity? Research design and methods: Interview based questionnaires were distributed to consecutive patients attending the Diabetes Clinic, Ninewells Hospital, Dundee over a period of five months. Exclusion criteria were age below 20 years and inadequate understanding of English; 428 questionnaires were given out with 406 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
258
7
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(283 citation statements)
references
References 24 publications
12
258
7
6
Order By: Relevance
“…Less physical activity may reflect the inertia of a lifetime of habits. These individuals likely have the same motivational barriers, including lack of interest and not enough time, as adults without diabetes (17,32,33). However, those with diabetes often have physical disabilities (34), per- ceive discomfort when exercising (33), or have decreased exercise capacity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Less physical activity may reflect the inertia of a lifetime of habits. These individuals likely have the same motivational barriers, including lack of interest and not enough time, as adults without diabetes (17,32,33). However, those with diabetes often have physical disabilities (34), per- ceive discomfort when exercising (33), or have decreased exercise capacity (35).…”
Section: Discussionmentioning
confidence: 99%
“…15 There is now extensive literature exploring perceived barriers or 'burdens' 8 to increasing physical activity, both in older groups generally, [15][16][17] and in people with type 2 diabetes in particular. 6,18,19 Barriers that have been identified include: poor health, lack of time, ageing, adverse environments; 17,20,21 safety/physical vulnerability, availability of facilities, cost, lack of motivation; 16,20 cultural norms and social expectations; 19 and difficulties exercising, tiredness, and being distracted by something good on television. 18 While previous research has focused on perceived benefits as well as barriers to being physically active, 16,22 the emphasis, to date, has tended to be on the latter.…”
Section: Introductionmentioning
confidence: 99%
“…6,18,19 Barriers that have been identified include: poor health, lack of time, ageing, adverse environments; 17,20,21 safety/physical vulnerability, availability of facilities, cost, lack of motivation; 16,20 cultural norms and social expectations; 19 and difficulties exercising, tiredness, and being distracted by something good on television. 18 While previous research has focused on perceived benefits as well as barriers to being physically active, 16,22 the emphasis, to date, has tended to be on the latter. But it is unlikely that simply removing barriers is in itself sufficient to enable people to undertake physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found younger subjects exercise more than older subjects [93,[98][99][100][101]. Plontikoff and colleagues in 2000 reported no significance difference between age groups.…”
Section: Confounders For Physical Activity Self-carementioning
confidence: 99%